Fracture Energy Measurement in Different Concrete Grades - Yip, C. L.; Mohamad, H. M.; Ahmad, H. (International Journal of Integrated Engineering, 2023)
Fracture energy is regarded as an intrinsic (material) property to dominate crack mechanisms and associated crack growth to concrete damage under applied stress. More recently, huge evolution in computing technology leading to finite element analysis (FEA) approaches to require incorporation of constitutive model, such as traction-separation relationship derived from state-of-the-art fracture mechanics fundamental. A physically-based models requires fracture energy values; therefore, properly measured fracture energy value is essential to exhibit better structures response within FEA models. Large arrays of parameters involved during concrete mixture such as beam size effect, aggregate size and concrete grade to affect the flexural resistance in concrete. The fracture and failure in concrete ahead of crack tip is represented by fracture energy values where micro-damage events occurred such as interfacial failure, fiber-bridging and matrix cracking. This study aims to investigate the fracture energy of concrete specimens with combination of notch depth ao at mid-span, design concrete strength as specified in the testing series. Independent compression strength, fc and measured load-displacement profiles under three-points bending test were used to determine fracture energy by incorporating three available fracture energy expressions such as Bazant, Hillerborg and CEB-FIP models.